Sperm Preservation using Freeze-Drying Method - TAKDIR SAILI; MULYOTO PANGESTU; MOHAMAD AGUS SETIADI; SRIHADI AGUNGPRIYONO; MOZES R. TOELIHERE; ARIEF BOEDIONO (HAYATI Journal of Biosciences, 2005)
Since the discovery of cryopreservation method for bull semen, cryopreservation become an alternative method for maintaining gamet resources of certain animal which is threatened or near extinction. This technology was then applied to the preservation of embryo, oocyte, ovary and testis. The application of intracytoplasmic sperm injection (ICSI) for which sperm motility is unnecessary had supported the effort to create simplified method such as freeze-drying for sperm preservation. Due to the benefit of ICSI over the conventional in vitro fertilization (IVF) the spermatozoon could be mechanically driven to pass through the zona pellucida and entering the cytoplasm of oocytes prior to fertilization. The freeze-drying method is an alternative method in sperm preservation which ignored the motility of sperm. The sperm resulted from this technique is in drying state, therefore, it might be stored in room temperature or in refrigerator. Many reports have claimed that freeze-dried sperm which is not motile but has an intact DNA was able to fertilize oocytes, even produced offspring in mouse.